A reappraisal of motivation and language learning strategies amongst undergraduate students of French as a foreign language - le Roux, Toni; Horne, Fiona (Journal for Language Teaching, 2025)
French has always been a minor discipline at universities in South Africa, despite its enormous socio-economic and professional potential on the African continent and in the Francophone world more generally. One of the main reasons for this is that few learners continue past the A1 (beginner) level, which may be attributed to low levels of motivation. This article explores the factors which impact student motivation and throughput in French undergraduate language courses at the University of the Witwatersrand in South Africa. The study, based on a master’s research project, was conducted between 2021 and 2023 and included questionnaires and interviews to evaluate students’ self-efficacy beliefs, motivations, levels of engagement and use of language learning strategies and the extent to which this impacted the continuation of their studies. The results showed that while both learning strategies and self-efficacy beliefs were present, these were not sufficient determinants for students to continue their language learning journey beyond the beginner level. The findings open a discussion on how to foster resilience in language learning at university level. More generally, they shed light on the limitations of instrumental motivation and a purely utilitarian approach to the teaching and learning of languages.